A Review of Influential Ideology in the Praxis of English Language Education for Junior High School Students in Indonesia - Rizky Syahra Putri (Raja Zulkarnain Education Foundation, 2026)
Education is undoubtedly the most important pillar in the development of a society, while philosophy is a body of knowledge that analyzes theories of knowledge. Consequently, philosophy cannot be separated from education because both contain precise goals to be achieved through education, including English language education. This study aims to explore the characteristics of contemporary philosophy that are relevant to the practice of English language education in Indonesia. This study uses a qualitative approach by conducting a systematic literature review to describe the ideologies that influence the practice of English language education in Indonesian Junior High Schools contained in online journal scientific articles. A total of ten online journal scientific articles were found and analyzed using a qualitative approach based on terms, statements, and paragraphs that describe the practice of English language education in Indonesia. The results of the study indicate that the characteristics of contemporary philosophy are relevant to the practice of English language education in Indonesia. To produce more convincing results, more longitudinal research is needed on the ideologies that influence English language education in Indonesia.